PENGARUH AUDIT INTERNAL DALAM PENCEGAHAN KECURANGAN KAS PADA PDAM TIRTA BUMI WIBAWA KOTA SUKABUMI - Ai Devi Srimulyani (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2020)
Ai Devi Srimulyani (043061211066) Universitas Muhammadiyah Sukabumi. The role of Internal Audit Effectiviness to Fraud Prevention in Cash at PDAM Tirta Bumi Wibawa Kota Sukabumi. (Adviser Ismet Ismatullah, SE., M.Ak., dan Dani Iswanto, SIP., MM.) This study aims to determine the role of internal audit to prevention fraud in cash. Variable used in this study is internal audit and fraud in cash. This research was carried out by using descriptive assosiatif methods, while the population in this study is all employes of PDAM Tirta Bumi Wibawa Kota Sukabumi and taken a sample of 62 people. The sampel in this study using the technique of simple random sampling. Data collected in this study by questionnaires, and literature and then methods used to process and analyze data in this study using validity test and reliability, normality test, simple linear regression analysis, t test as hypothesis testing for decision making and the coefficient of determination. Based on the results of research shows that the implementation of internal audit at PDAM Tirta Bumi Wibawa Kota Sukabumi is well-executed, it is in the show with the value of internal audit at 86%, and based on the results of t-test statistic scan be seen t count greater than t table is 2,747 > 2,000. With the test results to the coefficient of determination equal to 0,112 or 11,2%. Which means that the internal audit are able to influence the Fraud Prevention in Cash by 11,2% and 88,8% influence by other faction not examined by researcher.